Myelography in the Age of MRI: Why We Do It, and How We Do It. (10th February 2011) - Ozdoba, Christoph; Gralla, Jan; Rieke, Alexander; Binggeli, Ralph; Schroth, Gerhard
Abstract : Myelography is a nearly ninety-year-old method that has undergone a steady development from the introduction of water-soluble contrast agents to CT myelography. Since the introduction of magnetic resonance imaging into clinical routine in the mid-1980s, the role of myelography seemed to be constantly less important in spinal diagnostics, but it remains a method that is probably even superior to MRI for special clinical issues. This paper briefly summarizes the historical development of myelography, describes the technique, and discusses current indications like the detection of CSF leaks or cervical root avulsion.